The Eponyms and Inheritance of the Genetic Disorders of Pigmentation. Issue 3 (May 2016) - Chow, Maggie L.; Jacob, Sharon E.
Abstract : ABSTRACT: In clinical practice, the genetic disorders of pigmentation are often referred to by their eponyms, which are terms named after people or, occasionally, places or things ("Eponym, " 2014). This article will describe the eponyms, inheritance patterns, and key clinical features of the diseases and genetic disorders associated with aberrant pigmentation.